Exogenous Lipocalin 2 Ameliorates Acute Rejection in a Mouse Model of Renal Transplantation. Issue 3 (23rd November 2015) - Ashraf, M. I.; Schwelberger, H. G.; Brendel, K. A.; Feurle, J.; Andrassy, J.; Kotsch, K.; Regele, H.; Pratschke, J.; Maier, H. T.; Aigner, F.
Abstract: Lipocalin 2 (Lcn2) is rapidly produced by damaged nephron epithelia and is one of the most promising new markers of renal injury, delayed graft function and acute allograft rejection (AR); however, the functional importance of Lcn2 in renal transplantation is largely unknown. To understand the role of Lcn2 in renal AR, kidneys from Balb/c mice were transplanted into C57Bl/6 mice and vice versa and analyzed for morphological and physiological outcomes of AR at posttransplantation days 3, 5, and 7. The allografts showed a steady increase in intensity of interstitial infiltration, tubulitis and periarterial aggregation of lymphocytes associated with a substantial elevation in serum levels of creatinine, urea and Lcn2. Perioperative administration of recombinant Lcn2:siderophore:Fe complex (rLcn2) to recipients resulted in functional and morphological amelioration of the allograft at day 7 almost as efficiently as daily immunosuppression with cyclosporine A (CsA). No significant differences were observed in various donor–recipient combinations (C57Bl/6 wild‐type and Lcn2 −/−, Balb/c donors and recipients). Histochemical analyses of the allografts showed reduced cell death in recipients treated with rLcn2 or CsA. These results demonstrate that Lcn2 plays an important role in reducing the extent of kidney AR and indicate the therapeutic potential of Lcn2 in transplantation. Abstract : The authors demonstrate the function of lipocalin 2 as an upregulated marker during acute rejection and as a therapeutic agent to reduce acute rejection in a murine kidney transplantation model, supporting a possible future application of lipocalin 2 as an early biomarker as well as an immunosuppressive agent in kidney transplantation.